Mosaicism for a 12p12.1p12.2 microdeletion with a normal euploid cell line at amniocentesis in a pregnancy with a favorable outcome and postnatal decrease of the aneuploid cell line with microdeletion - Chih-Ping Chen; Fang-Tzu Wu; Yen-Ting Pan; Peih-Shan Wu; Wayseen Wang (Elsevier, 2023)
Objective: We present mosaicism for a 12p12.1p12.2 microdeletion with a normal euploid cell line at amniocentesis in a pregnancy with a favorable outcome and postnatal decrease of the aneuploid cell line with microdeletion. Case report: A 35-year-old woman, gravida 2, para 1, underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. Amniocentesis revealed mosaic 46,XY,del (12) (p11.2p12), and array comparative genomic hybridization (aCGH) revealed arr Xp22.31 × 2 mat, 12p12.2p12.1 × 1 [0.36]dn with a 4.15-Mb 36% mosaicism for a 12p12.1p12.2 microdeletion. At 22 weeks of gestation, she underwent cord blood sampling of which aCGH revealed arr Xp22.31 × 2 mat, 12p12.2p12.1 × 1 [0.34]dn with a 4.24-Mb 34% mosaicism for a 12p12.1p12.2 microdeletion. Prenatal ultrasound findings were unremarkable. She was referred for genetic counseling, and continuing pregnancy was advised. A 2990-g male baby was delivered at 38 weeks of gestation with no phenotypic abnormality. When follow-up at age 1½ months, the neonate was phenotypically normal. The karyotype of peripheral blood was 46,XY. aCGH analysis on the DNA extracted from peripheral blood revealed the result of arr 12p12.1p12.2 (20, 367, 240-24,489,386) × 1.87, arr Xp22.31 (6,488,721-8,097,511) × 2.0 [GRCh37 (hg19)] with 10-15% (log2 ratio = 0.1) mosaicism for a 4.122-Mb 12p12.1-p12.2 microdeletion encompassing 17 OMIM genes of PDE3A, SLCO1C1, SLCO1B3, SLCO1B1, IAPP, PYROXD1, RECQL, GOLT1B, SPX, GYS2, LDHB, KCNJ8, ABCCP, CMAS, C2CD5, ETNK1 and SOX5 and a 1.609-Mb Xp22.31 duplication encompassing two OMIM genes of STS and VCX. Interphase fluorescence in situ hybridization (FISH) analysis on 104 buccal mucosal cells using 12p12.1-specific probe showed 17% (18/104 cells) mosaicism for a 12p12.1 deletion. Polymorphic DNA marker analysis on the DNA extracted from proband's blood and parental bloods determined a paternal origin of the mosaic 12p12.1 deletion. Conclusion: Mosaicism for a 12p12.1p12.2 microdeletion at amniocentesis with a normal euploid cell line can be a benign condition in association with a favorable fetal outcome and postnatal decrease of the aneuploid cell line with microdeletion.